Reading, writing and comprehension: a possible challenge in virtual learning environments. (Cuidado y Ocupación Humana, 2025)
For a long time, experts and teachers have focused specifically on the teaching of reading, writing and comprehension, since they are fundamental for the school success and academic future of students who are not always facilitated in this domain. Precisely, this text originates from a study carried out at the Cazuca de Soacha Educational Institution with the purpose of improving these skills in first grade students using the online educational tool "Ludiletras" as support in the classroom. This study is situated within a qualitative methodology and the pedagogical action research (PAI) method, which aims to understand educational phenomena from a comprehensive perspective. 36 students participated in the sample, using different methods and tools to collect information, such as observation, recording notes in the field and diagnostic tests. This made possible an effective compilation of the investigations, thus generating reliable results that allowed the processing of the information and its corresponding analysis by triangulation. Likewise, this methodological triangulation approach allowed for greater comparison of the data collected, reducing risks of bias and guaranteeing the coherence of the results, which revealed findings that were grouped into four categories. Existing Lag (RE), Hidden Lag (RO), Common or Repetitive Lag (RCR) and Deep Lag (RP)..
Keywords: suicide; suicide attempt; adolescents; youths; risk factors